Fatty acid composition of bhallataka oil and their biological properties - VUSTELAMURI PADMAVATHI; BHATTIPROLU KESAVA RAO (International Journal of Pharma and Bio Sciences, 2017)
Semecrpus anacardium L.f is a plant well known for its therapeutic value in ayurvedic and siddha system of medicine, in our survey we found that, the Anacardiaceae family has 77 genera and 850 species surviving as trees, shrubs and vines. Out of these, the commonly known Cashew family (or) Sumac family has great viable importance. Due to the presence of several anticancer drugs isolated from Anacardiaceae family, we have selected Semecarpus anacardium L.f, for its high medicinal value in Ayurveda and Siddha systems and isolated numerous active constituents. In our research, Bhallataka oil (cape 32) found to have a free fatty acid (0.50) hence; alkaline Tran’s-esterification was done by using anhydrous methanol at a molar ratio of 6:1 and 3g/ Litre of sodium hydroxide as catalyst, and the results showed that Fatty acids with highest weight percentage 18:1 - 51.25403%, 16: 0 -13.41810%, 18:3 -6.042404% and also it consists of the antimicrobial activity against both gram positive and gram negative bacteria.